Impact on a fish assemblage of the maintenance dredging of a navigation channel in a tropical coastal ecosystem - Demarques Ribeiro da Silva Junior; Sérgio Ricardo Santos; Marcelo Travassos; Marcelo Vianna (Brazilian Journal of Oceanography, 2012)
Dredging and dredge-spoil disposal are among the major problems in coastal management. Many of the scientific contributions concerning the impacts of this practice are based on the study of sessile organisms and subtropical environments. We evaluated changes in the composition and abundance of a fish assemblage resulting from dredging and sediment disposal at the mouth and in the adjacent waters of the Caravelas River on the north-eastern coast of Brazil. Samples were collected in two directly impacted and three adjacent areas. Differences among stations were not significant, but the dredged site had the least diverse station, as expected. The stations farthest from the directly impacted areas apparently were not influenced by the coastal work, thus suggesting localised effects. The contribution of the present study is particularly important because of the study area's proximity to others that have high conservation value such as mangrove forests and coral reefs, and the relevance of the subject given the continuing dredging activity. A dragagem e descarte de sedimento se destacam como atividades que geram grandes distúrbios aos ecossistemas marinhos e, consequentemente tornam-se um desafio ao manejo e ordenamento costeiro. Grande parte dos estudos que abordam seus impactos é baseada em pesquisas com organismos sésseis e em ambientes temperados, criando uma lacuna no entendimento de seus efeitos sobre a ictiofauna, principalmente nas regiões tropicais. No presente estudo foram avaliadas as alterações na composição e abundância da comunidade de peixes sob influência da dragagem e descarte de sedimento na foz do Rio Caravelas, costa da região Nordeste do Brasil. As amostras foram obtidas em duas estações diretamente afetadas e em três outras áreas adjacentes. Não houve diferença significativa na diversidade média obtida para cada estação, porém a estação correspondente à área dragada apresentou o menor valor dentre as demais. As estações mais afastadas aparentemente não foram influenciadas pelo empreendimento sugerindo efeitos localizados. A contribuição do presente estudo é particularmente importante devido à proximidade com áreas de alto valor de conservação como manguezais e recifes de corais e a relevância do assunto, o qual trata de uma atividade que sugere expansão em vista do desenvolvimento da atividade portuária.